Minimal clinically important difference for impulse oscillometry in adults with asthma - Abdo, Mustafa; Kirsten, Anne-Marie; Mutius, Erika von; Kopp, Matthias; Hansen, Gesine; Rabe, Klaus F.; Watz, Henrik; Trinkmann, Frederik; Bahmer, Thomas (The European respiratory journal, 2023)
Impulse oscillometry (IOS) allows an effort-independent evaluation of small airway function in asthma. Unfortunately, well-determined minimal clinically important differences (MCIDs) for IOS measures are lacking. Here, we provide MCIDs for frequently used IOS measures, namely frequency dependence of resistance (FDR) and area of reactance (AX), in patients with asthma.